Assessing the Longitudinal Relationship between Theta-Gamma Coupling and Working Memory Performance in Older Adults. (14th September 2021) - Brooks, Heather; Mirjalili, Mina; Wang, Wei; Kumar, Sanjeev; Goodman, Michelle S; Zomorrodi, Reza; Blumberger, Daniel M; Bowie, Christopher R; Daskalakis, Zafiris J; Fischer, Corinne E; Flint, Alastair J; Herrmann, Nathan; et al.
Abstract: Theta-gamma coupling (TGC) is a neurophysiologic mechanism that supports working memory (WM). TGC is associated with N-back performance, a WM task. Similar to TGC, theta and alpha event-related synchronization (ERS) and desynchronization (ERD) are also associated with WM. Few studies have examined the longitudinal relationship between WM performance and TGC, ERS, or ERD. This study aimed to determine if changes in WM performance are associated with changes in TGC (primary aim), as well as theta and alpha ERS or ERD over 6 to 12 weeks. Participants included 62 individuals aged 60 and older with no neuropsychiatric conditions or with remitted Major Depressive Disorder (MDD) and no cognitive disorders. TGC, ERS, and ERD were assessed using electroencephalography (EEG) during the N-back task (3-back condition). There was an association between changes in 3-back performance and changes in TGC, alpha ERD and ERS, and theta ERS in the control group. In contrast, there was only a significant association between changes in 3-back performance and changes in TGC in the subgroup with remitted MDD. Our results suggest that the relationship between WM performance and TGC is stable over time, while this is not the case for changes in theta and alpha ERS and ERD.